Corbicula fluminae Population and Distribution in Pergau Lakes. Issue 1 (August 2020) - Syed Omar, Sharifah Aisyah; Rak, Aweng Eh; Hassan, Hasimah; Yusoff, Akrimah; Hajisamae, Sukree; Shukor, Aisah Md
Abstract: Pergau Lake was one of the spot for harvesting C. fluminae . However, C. fluminae harvesting was prohibited for several years before. Yet, the information on this clam compositions and distribution at this area is still unknown. Therefore, a survey has been done to determine the composition of C. fluminae at five points in Pergau Lakes. The method used for C. fluminae collection of 100m lines per station by boat. The weight per bucket and the size of C. fluminae (length, width and height) were measured using digital venier caliper. Five points were selected but only four points obtaining alive C. fluminae, while in others, only dead C. fluminae were found. There were also differences in the length, height and width of C. fluminae at each point. This shows that the growth rate and lifespan of C. fluminae at each point are different. Therefore, the periodically rotation harvesting method can reduce the mortality of C. fluminae and increase the socio-ecomonic activity in the area.